Reliability evaluation of a high slope reinforced by anchor based on the stochastic finite-element method: Case study - Xia Bian; Jiaxing Liu; Lichao Nie; Shenggang Ma; Wenbing Tao; Chengchun Qiu; Guizhong Xu (Case Studies in Construction Materials, 2023)
This study focuses on investigating the deformation and stability of high slopes under various working conditions to address the potential risks posed by slope collapse to both personal safety and infrastructure. By conducting a case study on a specific high slope project, the behavior of the slope is examined. Reliability theory is employed to analyze and calculate the probability of slope failure, in order to evaluate the slope's reliability and stability under three conditions: natural state, anchor and frame beam support, and anchor support. Analysis of field measured data reveals that the slope exhibits relatively stable behavior when supported by the anchor and frame beam. Reliability analysis of geotechnical parameters indicates that the cohesion, angle of internal friction, modulus of elasticity, and density of the surface geotechnical body have a greater influence on the results compared to other parameters. Using the stochastic finite element method to analyze and calculate the slope, the failure probability of the slope in its natural state is determined to be 35.9%. In contrast, the failure probability reduces to 1.3% for the anchor and frame beam support scheme and 6.1% for the anchor support scheme. These findings suggest that the anchor and frame beam support scheme demonstrates the most effective performance in terms of slope stability. The numerical simulation results validate the actual protective effect of the slope and offer valuable insights for similar slopes reinforced by anchor and frame beam systems.